? De novo Synthesis of Streptolysin S (SLS): Short Communication (Biological Sciences - PJSIR, 1994)
rial obtained from 'cells A' but at no higher dilutions, whereasa titre of 1000 HU/ml was found in material obtained from'cells B' which was suspended in induction buffer withoutadded chloramphenicol (Table 1).